Investigation of Conductivity, Flexibility, and Thermal Curing Effects in Hybrid Graphene Nanoplatelet–Silver–Carbon Black Inks - Mazilah Abu Bakar; Nor Azmmi Masripan; Chonlatee Photong; Alan Watson; Salim, Mohd Azli (International Journal of Integrated Engineering, 2026)
This paper presents a study on conductivity, flexibility and thermal curing effects on hybrid Graphene nanoplatelets-silver-carbon black conductive ink, aiming to optimize the inks performance for printed and flexible electronics. The hybrid conductive ink was formulated at room temperature and printed on the copper substrate using a manual stencil printing technique followed by thermal curing at 240 °C, 250 °C and 260 °C for five hours. The printed inks were subjected to cyclic bending tests and the electrical performance of the conductive ink was evaluated in terms of bulk resistance and resistivity. The results showed that samples cured at 260 °C exhibited the lowest initial average bulk resistance 2.1 Ω and resistivity 1.25 × 10⁻⁴ Ωm which indicate enhanced initial conductivity. However, after extended cyclic bending up to 16000 cycles, a significant increase in resistance to 3.7 Ω and resistivity 2.23 × 10⁻⁴ Ωm was observed. In contrast, samples cured at 250 °C initially showed higher average bulk resistance 3.4 Ω and resistivity 2.01 x 10-4 but experienced a significant decrease after 16,000 bending cycles to 1.8 Ω and 1.07 x 10-4 Ωm, suggesting possible conductive network reorganization under mechanical stress. Samples cured at 240 °C demonstrate moderate and more stable conductivity with less variation throughout the cycles, even the initial average bulk resistance 3.4 Ω and resistivity 2.01 x 10-4. In conclusion, these findings highlight the critical role of thermal curing in achieving optimal ink performance, where both electrical conductivity and flexibility must be balanced. An ideal curing temperature around 250 °C offers a practical compromise between low resistance and structural integrity for applications in printed and flexible electronics. Further study is recommended for samples cured at 250 °C to confirm the reproducibility of the observed resistivity reduction after long-term cyclic effects.